Stability and reliability of low voltage hybrid AC-DC microgrids power flow model in islanding operation - hasti afianti; Ontoseno Penangsang; Adi Soeprijanto (Institute of Advanced Engineering and Science, 2020)
The problem of decreasing and increasing power flow in hybrid AC-DC microgrids in island operations is the concern of this research. This condition arises if one sub-microgrid cannot supply load power requirements, either due to a decrease in power at the source or an increase in load on the sub-microgrid network. As a result, in this research used the bidirectional converter as an interlinking converter, the converter can change the power flow from the ac sub microgrid to the dc sub microgrid and vice versa. With this bidirectional converter, load power requirements can be met even though there is a power change in one of the sub microgrid. The simulation in this research support by Simulink/Matlab software. The model is built in a low voltage system, and the power flow analysis is in steady-state condition with two different cases. The simulation results show the stability and reliability of the power flow in both sub microgrid with stable frequency and voltage when power and load change occur.